1988
DOI: 10.3171/jns.1988.69.4.0518
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intracerebral hematoma location on the risk of brain-stem compression and on clinical outcome

Abstract: The clinical findings and computerized tomography (CT) brain scans of 45 patients with supratentorial intracerebral hematomas were evaluated to determine the effect of hematoma location on the clinical course and outcome of the disease. The lesions were frontal in 18 patients, temporal or temporoparietal in 17, and parieto-occipital in 10. No patient with a frontal or parieto-occipital hematoma had clinical signs of transtentorial herniation at admission or subsequently, whereas seven (41%) of those with tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(33 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…Most of our patients had large deep clots that were more likely than lobar hematomas to distort centrally situated structures which maintain alertness. Another study of lobar hematomas [6] found that tempo ral or temporoparietal clots larger than 30 cm-' were more often than frontal or occipital clots associated with signs of brainstem compression. There was also a corre lation between maximal midline shift (structure not slated) and clot volume in patients with temporal hem orrhages.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our patients had large deep clots that were more likely than lobar hematomas to distort centrally situated structures which maintain alertness. Another study of lobar hematomas [6] found that tempo ral or temporoparietal clots larger than 30 cm-' were more often than frontal or occipital clots associated with signs of brainstem compression. There was also a corre lation between maximal midline shift (structure not slated) and clot volume in patients with temporal hem orrhages.…”
Section: Discussionmentioning
confidence: 99%
“…In evaluation of patients with supratentorial ICH, Andrews et al 1) noted that head injury was the cause of the hematoma in six of the seven patients who developed brain stem compression. They mentioned that this might simply reflect the predominance of head injuries in this group.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this article, normal adult ICP is defined as 5 to 15 mm Hg (7.5-20 cm H 2 O). ICP values of 20 to 30 mm Hg represent mild intracranial hypertension; however, when a temporal mass lesion is present, herniation can occur with ICP values less than 20 mm Hg [5]. ICP values greater than 20 to 25 mm Hg require treatment in most circumstances.…”
Section: Normal Valuesmentioning
confidence: 99%